Analisis Efektivitas Dan Pengaruh Satuan Pengawasan Intern (SPI) Terhadap Kinerja Manajerial Pada Universitas Trunojoyo Madura - Moh. Wakit Ready; Mudji Kuswinarno; R.M. Mochammad Wispandono (Trunojoyo University of Madura, 2014)
The research aims to examine and analyze the effectiveness of internal auditor and the influence toward managerial performance in Trunojoyo University of Madura. Data collected through distribution of questionnaires and it is implemented to Trunojoyo University of Madura’s 55 managers. Analysis of data in this research using the help of SPSS version 16 for windows. A sampling technique uses stratified random sampling proportionally and data test technique is used within the research includes validity test by product moment correlation, reliability test with alpha cronbach. Classic assumption test, t one tail test and double linear regression analysis is used to verify and to prove the research hypothesis. Analysis result demonstrates that internal auditor done effectively and have a positive influence simultanly and partially toward managerial performance.